Efficacy of Ultrasound-Guided Glenohumeral Joint Injections of Leukocyte-Poor Platelet-Rich Plasma Versus Hyaluronic Acid in the Treatment of Glenohumeral Osteoarthritis: A Randomized, Double-Blind Controlled Trial. Issue 6 (17th November 2022) - Kirschner, Jonathan S; Cheng, Jennifer; Creighton, Andrew; Santiago, Kristen; Hurwitz, Nicole; Dundas, Mark; Beatty, Nicholas; Kingsbury, Dallas; Konin, Gabrielle; Abutalib, Zafir; Chang, Richard
Abstract : Objective: To compare the efficacy of ultrasound-guided hyaluronic acid (HA) versus leukocyte-poor platelet-rich plasma (LP-PRP) injection in the treatment of glenohumeral osteoarthritis. Design: Double-blind randomized controlled trial. Setting: Academic institution. Patients: Seventy patients with chronic glenohumeral osteoarthritis were randomly assigned to receive a single injection of HA (n = 36) or LP-PRP (n = 34). Interventions: Leukocyte-poor platelet-rich plasma was processed using Harvest/TerumoBCT Clear PRP kits. Ultrasound-guided injections of 6 mL HA or 6 mL LP-PRP into the glenohumeral joint were performed. Patients, the injecting physician, and outcomes assessor were blinded to treatment assignments. Main outcome measures: Shoulder Pain and Disability Index (SPADI), American Shoulder and Elbow Surgeons (ASES) score, current/average numerical rating scale (NRS) pain scores, satisfaction, and side effects were assessed at the 5 follow-up time points over 12 months. Results: Baseline characteristics were similar between groups. There were no significant between-group differences regarding SPADI, ASES, and current/average NRS pain scores at any time point up to 12 months postinjection ( P > 0.05). However, significant improvements in SPADI, ASES, and current/average NRS pain scores were observed in both groups starting at 1 or 2 months ( P < 0.01, P < 0.01, P < 0.001, and P < 0.01, respectively). These improvements were observed regardless of osteoarthritis severity. For patients who received LP-PRP, there was no effect of platelet yield on outcomes. Side effect and satisfaction rates were similar between groups. Conclusions: There were no differences in pain and functional outcomes after a single injection of LP-PRP versus HA. However, significant improvements in pain and function were observed after both treatments in patients with glenohumeral osteoarthritis.